2015
DOI: 10.1002/j.0022-0337.2015.79.4.tb05902.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mobile Device Optimized Cross Platform‐Compatible Oral Pathology and Radiology Spaced Repetition System for Dental Education

Abstract: Combining active recall testing with spaced repetition increases memory retention. The aim of this study was to evaluate and compare students' perception and utilization of an electronic spaced repetition oral pathology-radiology system in dental hygiene education and predoctoral dental education. The study employed an open-source suite of applications to create electronic "lashcards" that can be individually adjusted for frequency of repetition, depending on a user's assessment of dificulty. Accessible across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Consistent with this study, there is evidence to show that learners who self‐engaged in active question‐based learning had improved outcomes in academic performance compared to passive methods . In addition, spaced repetition, the order in which questions are visited and how often they are reviewed, remains highly important for memory retention and improved academic performance . Specifically, this study utilized new and review questions that allowed users to be introduced to new content but also to review questions they had answered incorrectly more often than the questions they answered correctly.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Consistent with this study, there is evidence to show that learners who self‐engaged in active question‐based learning had improved outcomes in academic performance compared to passive methods . In addition, spaced repetition, the order in which questions are visited and how often they are reviewed, remains highly important for memory retention and improved academic performance . Specifically, this study utilized new and review questions that allowed users to be introduced to new content but also to review questions they had answered incorrectly more often than the questions they answered correctly.…”
Section: Discussionsupporting
confidence: 54%
“…Hard‐copy textbooks have historically been the gold standard; however, electronic media continues to grow with the newer generation of medical professionals . Smartphone, tablet, and web‐based presentation of question banks, readings, and clinical vignettes have been shown to be helpful in delivering educational content to trainees . For example, Hsueh et al recently published improvement in otolaryngology OTE performance for junior residents when using a mobile app platform that allowed primary literature resource sharing and associated multiple‐choice questions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half of the empirical research articles (n = 48, 47%) did not explicitly mention a theoretical framework. In total, nine theoretical frameworks were mentioned in the remaining studies of which the Spacing effect (n = 40) and Testing effect (n = 31) were named most often. Other frameworks were Cognitive Load Theory (n = 4), Desirable Difficulties Theory (n = 2), Retrieval hypothesis (n = 2), Total‐time hypothesis (n = 2), Learning Theory (n = 1), Metacognitive Theory (n = 1) and Kolb's Experiential Learning Theory (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from the study revealed that LC system provided excellent enhancement of learning by improving communication between teacher and student X DISCUSSION E-learning may be defined as any use of computers and networks in education in which the instructional content is delivered electronically as required by the learner [6]. The other synonyms used for e-learning are web-based learning, online learning, computerassisted instruction, computer-assisted learning, and Internet-based learning [14][15][16]. During the initial search process of the review many of the above-mentioned synonyms were used to get the maximum number of the articles about this specific topic.…”
Section: [13]mentioning
confidence: 96%